University courses on cultural management as educational opportunities for the Catholic Church: some reflections based on teaching experience - Banús, Enrique (Church, Communication and Culture, 2018)
A relevant part of the global cultural heritage has a religious dimension. A good part of it belongs to the culture inspired by the Catholic Church. This article reflects on the teaching experiences of an academic course on cultural management held regularly at a Pontifical university in Rome. The main argument of the paper is that cultural heritage of religious interest, when integrally presented, can be a relevant approach to evangelization. Professional knowledge, expertise and awareness of this evangelizing potential should be combined in order to present religious heritage in its full sense. Academic and pastoral mediation can help to manifest the religious dimension of the Christian heritage and to educate the audience in understanding it correctly.